2014
DOI: 10.1016/j.scr.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

CD34+/CD45-dim stem cell mobilization by hyperbaric oxygen — Changes with oxygen dosage

Abstract: Because hyperbaric oxygen treatment mobilizes bone marrow derived-stem/progenitor cells by a free radical mediated mechanism, we hypothesized that there may be differences in mobilization efficiency based on exposure to different oxygen partial pressures. Blood from twenty consecutive patients was obtained before and after the 1st, 10th and 20th treatment at two clinical centers using protocols involving exposures to oxygen at either 2.0 or 2.5 atmospheres absolute (ATA). Post-treatment values of CD34+, CD45-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Ratios appear to have value for predicting healing within 16 weeks, but the functional relevance of the HIF ratio is unknown. Prior work has suggested that SPCs with higher content of HIF-1 and -2 are those primed for prompt mobilization from the bone marrow; these cells may be preferentially sequestered in the peripheral vasculature; and lower HIF levels in circulating SPCs might occur due to protein degradation (15,19,34). The similarities in HIF ratios across 8 weeks (Supplementary Table 3) suggest that chronological age since mobilization and perhaps stresses sustained by the cells were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratios appear to have value for predicting healing within 16 weeks, but the functional relevance of the HIF ratio is unknown. Prior work has suggested that SPCs with higher content of HIF-1 and -2 are those primed for prompt mobilization from the bone marrow; these cells may be preferentially sequestered in the peripheral vasculature; and lower HIF levels in circulating SPCs might occur due to protein degradation (15,19,34). The similarities in HIF ratios across 8 weeks (Supplementary Table 3) suggest that chronological age since mobilization and perhaps stresses sustained by the cells were similar.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that wound healing can be improved by increasing the number of circulating SPCs and/or enhancing wound site recruitment (2,7,16,17). There also is evidence that some adjuncts to standard treatment such as negative pressure dressings and hyperbaric oxygen will mobilize SPCs to blood and may also modify regulatory protein content that improves vasculogenic function (11,15,18,19). Pharmacological agents that might be used incidental to DFU treatment or as an adjunct may also influence SPCs (2032).…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications have reported variable outcomes in great part because of using protocols that differ significantly in depth, duration, frequency and number of sessions [36][37][38]. It appears that HBOT can be effective in decreasing chronic inflammation in the brain by reducing pro-inflammatory cytokine activation and through provocation of stem cell activity [7][8][9][10]. The repeat brain SPECT indicated the valuable contribution of this technique as a functional imaging biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The treatments included 1) hyperbaric oxygen therapy (HBOT), 2) combination therapy of infused ketamine concurrent with transcranial magnetic stimulation (TMS), 3) injections of perispinal etanercept (PSE), and 4) non-invasive trans-nasal Sphenopalatine Ganglion (SPG) block. HBOT is believed to have anti-inflammatory effects, reducing the excess of proinflammatory cytokine activation such as TNF-alpha and facilitating improvement by provocation of stem cell activity [7][8][9][10]. The combination therapy of infused ketamine administered concurrent to TMS appears to address the abnormalities in brain circuits found both in treatment resistant depression and treatment resistant central pain [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The Undersea and Hyperbaric Medical Society indicates the use of HBOT for several conditions, including decompression sickness, acute thermal burns, arterial insufficiencies, refractory osteomyelitis, and compromised grafts and flaps as well as necrotising and anaerobic soft tissue infections . In addition, new studies have revealed a possible regenerative component to HBOT therapy where the release of progenitor cells has been demonstrated with its use . While HBOT has advocates and numerous studies, and randomised clinical trials point to its efficacy, HBOT occasionally causes vasoconstriction, cellular toxicity and tissue damage .…”
Section: Introductionmentioning
confidence: 99%